EFL PRE-SERVICE TEACHERS’ PERCEPTION TOWARD THE USE OF MOBILE ASSISTED LANGUAGE LEARNING IN TEACHING ENGLISH - Nariyati, Ni Putu Linda; Sudirman, Sudirman; Pratiwi, Ni Putu Astiti (Universitas Negeri Makassar, 2020)
In 21st century, educational process has been changed by the development of technology. One of the strategies that can be applied to support educational process in digital era is that the use of Mobile Learning strategy. Related to language learning, Mobile learning is further developed into the term Mobile Assisted Language Learning (MALL). This study aimed at investigating EFL pre-service teachers? perception toward the use of Mobile Assisted Language Learning in teaching English as Foreign Language. Explanatory sequential mixed method design was used as the method of this study. The participants of this study were 70 participants from semester 8 students of English Language Education in Ganesha University of Education. Data of this study were collected through questionnaire and interview. As the result, EFL pre-service teachers had positive perceptions toward the use of MALL in teaching English. It shows that EFL pre-service teachers understand and aware toward MALL in teaching English.